Cancer Progression Gene Expression Profiling Identifies the Urokinase Plasminogen Activator Receptor as a Biomarker of Metastasis in Cutaneous Squamous Cell Carcinoma - Minaei, Elahe; Mueller, Simon A.; Ashford, Bruce; Thind, Amarinder Singh; Mitchell, Jenny; Perry, Jay R.; Genenger, Benjamin; Clark, Jonathan R.; Gupta, Ruta; Ranson, Marie (Frontiers in Oncology, 2022)
Cutaneous squamous cell carcinoma (cSCC) is the second most prevalent skin cancer, with metastases to regional lymph nodes occurring in 2-5% of cases. Dysregulated pathways affecting extracellular matrix remodeling, cell motility and survival have been associated with cSCC invasiveness. We conducted targeted cancer progression gene expression and pathway analysis in non-metastasizing (PRI-) and metastasizing primary (PRI+) head and neck cSCC tumors, cognate lymph node metastases (MET) and matched sun-exposed skin (SES) to elucidate molecular events characterising cSCC invasion and metastasis and identify potential therapeutic targets. Cancer progression pathways and cell functions promoting matrix remodeling, cell motility, cell survival, and angiogenesis were significantly activated in metastasising tumors (MET and PRI+) compared to non-metastasising tumors (PRI-) and SES. The highest differentially expressed genes, including PLAU, PLAUR, MMP1, MMP10, MMP13, ITGA5, VEGFA and various inflammatory cytokine genes, conceptually link matrix remodeling, cell adhesion/migration and epithelial to mesenchymal transition with tumor progression and an invasive phenotype. Ingenuity Pathway Analysis of differential gene expression profiles between tumor cohorts implicated EGF, VEGFA and IL1RA as important upstream regulators of these cSCC progression genes differentiating metastatic from non-metastatic tumors. In an extended patient cohort, urokinase plasminogen activator receptor (uPAR, encoded by PLAUR) immunohistochemistry demonstrated higher staining intensity in metastasizing tumors, which was negatively correlated with expression of hsa-miR-340-5p implicating this microRNA as a potential negative regulator of PLAUR. The effect of EGF on uPAR levels and cell motility was validated in human metastatic head and neck cSCC cells. Together, these results support uPAR as a key driver of metastasis and as a potential therapeutic target in cSCC.